Coevolution of relationship networks and resistance behaviors for building information modeling implementation in construction projects - Shao, Shiting; Cao, Dongping (International journal of project management, 2024)
•Using longitudinal network modeling to explore network-behavior dynamics for BIM implementation in construction projects.•Resistance behaviors impact the formation of communication and advice ties and result in network homogeneity through social selection.•Communication and advice ties in the networks impact the assimilation of individual resistance behaviors through social influence.•Communication ties have more significant effects on behavior assimilation than advice ties.•Network-behavior dynamics are also impacted by other node-level covariate effects and network structural effects. Heterogeneous individual participants are embedded within multiple dynamic intra-project relationship networks, which can both shape and be shaped by individual behaviors through social influence and selection processes, respectively. Yet empirical research on these complex interrelationships within projects remains lacking. This study fills this lacuna by investigating how formal task-oriented communication and informal knowledge-oriented advice networks coevolve with individual resistance behaviors for building information modeling (BIM) implementation in construction projects through social selection and influence processes. Stochastic actor-oriented network models and longitudinal data on project-level BIM implementation practices are used to examine this question. After controlling for related covariate and structural effects, the results provide clear evidence for the social selection process in which communication and advice ties in the networks are both more frequently formed between project participants with more similar resistance behaviors. Concerning the social influence process, the results show that compared with knowledge-oriented advice ties, task-oriented communication ties tend to more significantly influence the assimilation of resistance behaviors. The network-behavior coevolution process is simultaneously associated with the covariate effects related to individual experience as well as the structural effects related to reciprocity and triadic closure. As a pioneering effort of using longitudinal network modeling methods to empirically characterize network-behavior dynamics in projects, this study provides a deepened understanding of how social selection and influence processes collectively shape the dynamic interactions among heterogeneous project participants as a complex adaptive system.